A Novel MYH9-RET Fusion Occurrence and EGFR T790M Loss as an Acquired Resistance Mechanism to Osimertinib in a Patient with Lung Adenocarcinoma: A Case Report - Sun Y (OncoTargets and Therapy, 2020)
Yanwei Sun,1 Lina Pei,2 Ningning Luo,3 Dongsheng Chen,3 Lingxin Meng1 1Department of Oncology, People’s Hospital of Rizhao, Rizhao, People’s Republic of China; 2Department of Pharmacy, People’s Hospital of Rizhao, Rizhao, People’s Republic of China; 3The State Key Laboratory of Translational Medicine and Innovative Drug Development, Jiangsu Simcere Diagnostics Co., Ltd, Nanjing, People’s Republic of ChinaCorrespondence: Lingxin MengDepartment of Oncology, People’s Hospital of Rizhao, Rizhao, People’s Republic of ChinaEmail menglingxinrz@126.comBackground: Osimertinib is a novel and irreversible epidermal growth factor receptor (EGFR)-tyrosine kinase inhibitor (TKI) targeting EGFR sensitive mutations and EGFR exon20 p.T790M mutation, which demonstrated superior progression-free survival (PFS) and overall survival (OS).Case Presentation: We report a patient with lung adenocarcinoma harboring EGFR exon 19 deletion mutant treatment with icotinib. After 6 months, she developed EGFR exon20 p.T790M and then the patient received osimertinib treatment. A novel MYH9 (exon41)-RET (exon12) fusion and EGFR exon20 p.T790M loss were identified using plasma circulation tumor DNA (ctDNA) after osimertinib treatment, which led to rapid progression after osimertinib five months and suggested a potential resistance mechanism.Conclusion: Our findings expanded the spectrum of RET arrangement types and provided the basis for this hypothesis: acquired RET rearrangement and EGFR exon20 p.T790M loss potentially serve an additional resistance mechanism to osimertinib in EGFR-mutated non-small-cell lung cancer (NSCLC).Keywords: MYH9-RET fusion, EGFR exon20 p.T790M loss, lung adenocarcinoma, acquired resistance, osimertinib